2015
DOI: 10.11648/j.sjcm.s.2015040401.11
|View full text |Cite
|
Sign up to set email alerts
|

Prostate carcinoma: correlation of histopathology with serum prostate specific antigen

Abstract: Prostate Specific Antigen (PSA) is the first line test in screening of prostate cancer. The increase in PSA depends on differentiation of tumour cells. Gleason grading is one of the most powerful predictors of biological behaviour and influential factors used to determine treatment. PSA, when combined with Gleason score and clinical stage, improves the prediction of pathological stage for prostate carcinoma. Aims of this study were to study the histopathological features and Gleason grading in Prostatic Carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…13 The integrity of the prostatic tissue is lost by the undergoing various pathological processes, which are responsible for the release of prostate-specific antigen (PSA) into blood circulation, and there is an increase in the serum PSA lavels. 14,15 The increase in PSA values also depends on upon the differentiation of tumor cells. 16 About 80% of histologically proven adenocarcinoma have the serum PSA level > 4ng/ml, and it is evident in 25 -30% with nodular hyperplasia, prostatitis, infarcts, prostatic massage or cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…13 The integrity of the prostatic tissue is lost by the undergoing various pathological processes, which are responsible for the release of prostate-specific antigen (PSA) into blood circulation, and there is an increase in the serum PSA lavels. 14,15 The increase in PSA values also depends on upon the differentiation of tumor cells. 16 About 80% of histologically proven adenocarcinoma have the serum PSA level > 4ng/ml, and it is evident in 25 -30% with nodular hyperplasia, prostatitis, infarcts, prostatic massage or cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Wadgaonkar et al and Gurumurthy et al reported findings similar to our study with significant elevation in serum PSA levels in PIN and prostate carcinoma patients. 21,16 Serum PSA levels more than 10 ng/ml is highly indicative of prostate cancer. So, patients having PSA >10 ng/ml should be considered for surgical intervention as early as possible because of high probability of prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Shetty et al reported BPH in only 36.6% patients, prostatitis in 30%, PIN in 15.3% and carcinoma in 18% patients 15. Gurumurthy et al reported PIN in 5.95% cases of prostatic lesions 16. Horninger et al reported frequency of PIN in 2.91% patients and Anderson-Jackson et al in 4.07% patients, respectively.…”
mentioning
confidence: 99%
“…[20] Our study results were in concordance with other studies which found a statistically significant assosciation between higher Gleason score and increased sPSA levels. [36][37][38]Studies across globe also showed that there is statistically significant correlation between Gleason score and proportion of cells expressing Ki67 except in one study by Munoz E et al who concluded that they didn't find significant relation between Ki67 and Gleason score which may be due to smaller sample size. [26] Our study which included 100 cases of CaP is in concordance with other studies.…”
Section: Discussionmentioning
confidence: 99%